Groupthink Phenomenon as a Common Occurrence in Juvenile Gangs - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
In this presentation, groupthink phenomenon is defined. Its symptoms specified in the related literature are cited. Then, a typical youth gang is related to each of those specific symptoms. The result depicts a high probability that such a gang may fall into groupthink, indeed! (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Juvenile; gang; groupthink; cohesive